2021
DOI: 10.1186/s13058-021-01395-x
|View full text |Cite
|
Sign up to set email alerts
|

Infiltrating immune cells in benign breast disease and risk of subsequent invasive breast cancer

Abstract: Background It is well established that tumors are antigenic and can induce an immune response by the host, entailing lymphocytic infiltration of the tumor and surrounding stroma. The extent and composition of the immune response to the tumor, assessed through evaluation of tumor-infiltrating lymphocyte counts, has been shown in many studies to have prognostic and predictive value for invasive breast cancer, but currently, there is little evidence regarding the association between infiltrating i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…This method was developed by Pruneri et al [ 20 ] for DCIS and other pre-malignant lesions, supported by the recent guidelines of the International Immuno-Oncology Biomarker Working group [ 23 ]. The method was also recently utilised for benign breast disease [ 21 ]. Since the B3 lesions are not tumour, the term used in this manuscript is stromal lymphocytes instead of TILs.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This method was developed by Pruneri et al [ 20 ] for DCIS and other pre-malignant lesions, supported by the recent guidelines of the International Immuno-Oncology Biomarker Working group [ 23 ]. The method was also recently utilised for benign breast disease [ 21 ]. Since the B3 lesions are not tumour, the term used in this manuscript is stromal lymphocytes instead of TILs.…”
Section: Methodsmentioning
confidence: 99%
“…1 Step wise method for the evaluation of stromal lymphocytes of B3 lesions on H&E biopsy sections. This method of counting TILs from benign breast disease has recently been published by International Immuno-Oncological Working group ( www.tilsinbreastcancer.org ) [ 26 ] …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This method was developed by Pruneri et al [19] for DCIS and other pre-malignant lesions, supported by the recent guidelines of the International Immuno-Oncology Biomarker Working group [22]. Very recently the method was also utilised for benign breast disease [20]. Since the B3 lesions are not tumour, the term used in this manuscript is stromal lymphocytes instead of TILs.…”
Section: Assessing Stromal Lymphocytes On Hande Stained Sectionsmentioning
confidence: 99%
“…Higher TILs positively correlated with favourable prognosis and overall improved survival in triple negative and HER2 positive IBC [16, 17]. Studies on TILs have shed some light on the immune microenvironment of DCIS and benign breast disease, although the utility of TILs as a recurrence biomarker has not been consistent [1820]. A very recent study evaluated TILs in DCIS from the COMET trial and found that a higher number of TILs correlated with the upgrade rate of LG DCIS to HG DCIS [21].…”
Section: Introductionmentioning
confidence: 99%